An evaluation of the curriculum of Saint John the Apostle Academy and its implications to administrative concerns and directions - Neri, Florecita R., A.M.P. (Animo Repository, 1996)
The study evaluates the Agro-Industrial-Secondary Curriculum of Saint John the Apostle Academy since its operation from school year 1986-1987 to 1994-1995 using Stufflebeam's Context, Input, Process, Product (CIPP) evaluation model. Respondents in this study were two hundred (200) students coming from one section per year level, thirteen (13) faculty members, one hundred fifteen (115) graduates of SJAA from school year 1989 to 1995 who were available during the survey. Information/records/documents were made available by keypersons from identified organizations/institutions. Instruments and documents were the two sources of data. Documentary review was done to analyze the profile/needs of the municipality of Labo, school's philosophy, objectives, curriculum, faculty profile and the graduates' social/church involvement. Self-administered questionnaires were disseminated for the inventory of facilities, curriculum evaluation and for the graduates. Descriptive statistics such as means, frequencies and percentages were employed for the statistical analysis of data. The findings showed that Saint John the Apostle Academy's curriculum is responsive to the demands/needs of the community of Labo. SJAA has been faithful to its essence as a mission school and it develops the practical skills of poor students through different vocational training courses. The school's curriculum is consistent with its special features, spelled out in its philosophy and objectives. SJAA graduates are prepared for undertaking livelihood activities. Graduates have developed leadership skills / qualities and service-orientation as manifested in their social/church involvement.